Credit, Labor Informality and Firm Performance in Colombia - Lorena Caro; Arturo Galindo; Marcela Melendez (Inter-American Development Bank (IDB), 2012)
This paper explores the links between labor formality, access to credit and firm performance in Colombia using Annual Manufacturing Survey data for the period 2000-2009. A significant though small relationship is found between access to credit and informality. The results suggest that a 10 percent increase in the ratio of credit to sectoral output increases labor formality between 0. 76 and 1. 14 percentage points. This effect vanishes as a firms financial constraint increases. The paper also reports a strong correlation between labor formality and firm performance measured as output and employment growth. A one percentage point increase in labor formality is associated with an 8. 5 percent increase in output and an 11 percent increase in employment growth.
Keywords: E26; G21; O16; O4; 330